Noninvasive In-Situ Measurement of Blood Lactate Using Microwave Sensors - Mason, A.; Korostynska, O.; Louis, J.; Cordova-Lopez, L. E.; Abdullah, B.; Greene, J.; Connell, R.; Hopkins, J. (IEEE transactions on biomedical engineering, 2018)
Goal: This paper reports a novel electromagnetic sensor technique for real-time noninvasive monitoring of blood lactate in human subjects. Methods: The technique was demonstrated on 34 participants who undertook a cycling regime, with rest period before and after, to produce a rising and falling lactate response curve. Sensors attached to the arm and legs of participants gathered spectral data, blood samples were measured using a Lactate Pro V2; temperature and heart rate data was also collected. Results: Pointwise mutual information and neural networks are used to produce a predictive model. The model shows a good correlation (R = 0.78) between the standard invasive and novel noninvasive electromagnetic wave based blood lactate measurements, with an error of 13.4% in the range of 0-12 mmol/L. Conclusion: The work demonstrates that electromagnetic wave sensors are capable of determining blood lactate level without the need for invasive blood sampling. Significance: Measurement of blood metabolites, such as blood lactate, in real-time and noninvasively in hospital environments will reduce the risk of infection, increase the frequency of measurement and ensure timely intervention only when necessary. In sports, such tools will enhance training of athletes, and enable more effecting training regimes to be prescribed.